2021
DOI: 10.1183/23120541.00145-2020
|View full text |Cite
|
Sign up to set email alerts
|

The Living with Pulmonary Fibrosis questionnaire in progressive fibrosing interstitial lung disease

Abstract: The Living with Idiopathic Pulmonary Fibrosis (L-IPF) questionnaire was developed with substantial input from patients with IPF to assess symptoms and health-related quality of life (HRQoL). Because IPF is the prototypical chronic fibrosing interstitial lung disease (ILD) with a progressive phenotype, we expanded applicability of the L-IPF by deleting the word “idiopathic”, creating the L-PF (Living with Pulmonary Fibrosis) questionnaire, and then assessed its relevance among patients with progressive fibrosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…Limited data reported the humanistic burden of PF-ILD. Those studies identified showed that non-IPF PF-ILD negatively impacts both patients' and unpaid carers' quality of life (QoL), affecting their mental and physical health (9,11,19,31,32). These results are summarized below.…”
Section: Humanistic Burden Of Non-ipf Pf-ildmentioning
confidence: 99%
See 3 more Smart Citations
“…Limited data reported the humanistic burden of PF-ILD. Those studies identified showed that non-IPF PF-ILD negatively impacts both patients' and unpaid carers' quality of life (QoL), affecting their mental and physical health (9,11,19,31,32). These results are summarized below.…”
Section: Humanistic Burden Of Non-ipf Pf-ildmentioning
confidence: 99%
“…In the Living with Pulmonary Fibrosis (L-PF) study (n = 20), common symptoms reported by patients included dyspnea (95.0%), cough (95.0%), and fatigue (90.0%) (9). Similarly, patients in the King's Brief Interstitial Lung Disease (K-BILD) study (n = 20), commonly reported dyspnea (100.0%), chest tightness (85.0%), and chest wheezing/whistling (80.0%) (32).…”
Section: Symptomsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Living with IPF questionnaire (L-IPF) (107), developed in the English language, has published initial validation data in a cohort of patients with IPF and has recently expanded applicability as the Living with Pulmonary Fibrosis questionnaire (L-PF) (108). The Patient Experiences and Satisfaction with Medications questionnaire (PESaM) is a unique instrument evaluating patients' expectations, experiences, and satisfaction with disease-modifying drugs (109,110).…”
Section: Disease-specific Hrqol Promsmentioning
confidence: 99%